2001
DOI: 10.1046/j.1523-1755.2001.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of uremic serum on isolated cardiac myocyte calcium cycling and contractile function.

Abstract: These data show that one or more substances are present in uremic sera that acutely cause increased force of contraction and impaired recovery of cardiac myocyte calcium concentration as well as impaired relaxation. As these effects are similar to that seen with ouabain and can be prevented by co-incubation with an antibody fragment to digitalis, which also attenuates the sodium pump inhibitory effect, we suggest that this (these) substance(s) circulating in uremic sera and inhibiting the sodium pump also caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 34 publications
1
41
0
1
Order By: Relevance
“…Details of the method of isolation and culture of calcium-tolerant adult myocytes may be found in several recent reports from our laboratory (9,10,12). This method of isolation produced a good yield of rod-shaped (70 to 80%) myocytes in each of the experimental groups presented here.…”
Section: Isolation and Culture Of Cardiac Myocytesmentioning
confidence: 73%
See 4 more Smart Citations
“…Details of the method of isolation and culture of calcium-tolerant adult myocytes may be found in several recent reports from our laboratory (9,10,12). This method of isolation produced a good yield of rod-shaped (70 to 80%) myocytes in each of the experimental groups presented here.…”
Section: Isolation and Culture Of Cardiac Myocytesmentioning
confidence: 73%
“…Recent work suggests that echocardiographically demonstrable diastolic dysfunction is extremely common in ESRD patients treated with hemodialysis (30). As discussed briefly in the introduction, we have observed that sodium pump inhibition, which appears to accompany the chronic renal failure state, may acutely cause or contribute to both diastolic dysfunction and cardiac hypertrophy (7,10). To gain further insights into this issue we conducted the current study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations